Natural selection in human populations. - D.F. Roberts and; G. A.Harrison (New York, Estados Unidos : Pergamon Press, 1959)
"For the first full meeting of the newly formed Society for the Study of Human Biology, it seemed appropriate to address that biological field in which the most notable recent progress has been made: human genetics. Since the meeting was held in 1958, the centenary of the publication of Darwin-Wallace's work, it seemed particularly appropriate to choose natural selection as the topic. Accordingly, a symposium entitled "Natural Selection in Man" was held in the Anatomy Theater of University College London on November 8, 1958". (Copiado del prefacio).
1. Natural selection in man: some basic problems. 2. Mathematical models for selection. 3. The relative fitness of human mutant genes. 4. Natural selection and some polymorphc characters. 5. On selection of gene systems in natural populations. 6. Rate of change in primate evolution.
Keywords: BIOLOGÍA